2005
DOI: 10.1091/mbc.e04-12-1087
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PI3K and MAPK Signaling in bcl-2-induced Vascular Endothelial Growth Factor Expression in Melanoma Cells

Abstract: We have previously demonstrated that bcl-2 overexpression in tumor cells exposed to hypoxia increases the expression of vascular endothelial growth factor (VEGF) gene through the hypoxia-inducible factor-1 (HIF-1). In this article, we demonstrate that exposure of bcl-2 overexpressing melanoma cells to hypoxia induced phosphorylation of AKT and extracellular signal-regulated kinase (ERK)1/2 proteins. On the contrary, no modulation of these pathways by bcl-2 was observed under normoxic conditions. When HIF-1␣ ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 42 publications
4
63
0
Order By: Relevance
“…In 4T1 cells, ras-induced VEGF secretion was partly inhibited by either a MEK inhibitor or a PI3K inhibitor, but was markedly inhibited by both when given together, i.e., we could see the synergistic effect of both pathways in the expression of VEGF in tumor cells. Such synergism from the use of PI3K and MAPK inhibitors has been reported when angiogenic factors were induced in myeloma, melanoma, and gastric cancer cells (42)(43)(44).…”
Section: Regulation Of Vegf Expression By Mapk and Pi3k In Tumor Cellsmentioning
confidence: 55%
“…In 4T1 cells, ras-induced VEGF secretion was partly inhibited by either a MEK inhibitor or a PI3K inhibitor, but was markedly inhibited by both when given together, i.e., we could see the synergistic effect of both pathways in the expression of VEGF in tumor cells. Such synergism from the use of PI3K and MAPK inhibitors has been reported when angiogenic factors were induced in myeloma, melanoma, and gastric cancer cells (42)(43)(44).…”
Section: Regulation Of Vegf Expression By Mapk and Pi3k In Tumor Cellsmentioning
confidence: 55%
“…This suggests that NF-kB transcriptional activity is decreased upon downregulation of IL-8 signaling in hypoxic cells and provides a mechanism that may explain the increased sensitivity of hypoxic prostate cancer cells to etoposide when IL-8 signaling is impaired. Other studies from our laboratory have confirmed that IL-8 signaling potentiates NF-kB-mediated transcription of antiapoptotic genes (Wilson et al, in preparation) and activates the phosphoinositide-3 kinase (PI3K)/Akt and mitogenactivated protein kinase (MAPK) signaling cascades in PC3 cells (MacManus et al, 2007), pathways that are central to cell survival (Takami et al, 2002;Heidemann et al, 2003) and whose activity is increased in hypoxic cells (Trisciuoglio et al, 2005). Therefore, we suggest that IL-8 signaling may enable the survival of hypoxic prostate cancer cells and that strategies to inhibit IL-8 signaling may be a therapeutic option to sensitize hypoxic prostate cancer cells to conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 78%
“…While tumor cells express VEGF necessary for the chemotaxis of endothelial cells into the growing tumor tissue, the process of wound angiogenesis is dependent on endogenously expressed VEGF produced by various cells, including macrophages and keratinocytes [13,27]. Thus, inactivation of Akt causes inhibition of VEGF expression as has been reported by several groups [29,33,38,41]. In turn, reduced VEGF levels seem to be responsible for defective angiogenesis in wounds of Akt1 -/-mice.…”
Section: Discussionmentioning
confidence: 81%